2012
DOI: 10.1111/j.1472-4669.2012.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Inside the alkalinity engine: the role of electron donors in the organomineralization potential of sulfate‐reducing bacteria

Abstract: Mineral precipitation in microbial mats may have been the key to their preservation as fossil stromatolites, potentially documenting evidence of the earliest life on Earth. Two factors that contribute to carbonate mineral precipitation are the saturation index (SI) and the presence of nucleation sites. Both of these can be influenced by micro-organisms, which can either alter SI through their metabolisms, or produce and consume organic substances such as extracellular polymeric substances (EPS) that can affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
134
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 86 publications
(169 reference statements)
8
134
0
1
Order By: Relevance
“…As outlined above, this pattern can easily be attributed to changes in fermentation patterns yielding different organic substrates (e.g., organic acids) available to the sulfate-reducing population. This change could have a major impact on the CaCO 3 precipitation by the microbial community [61,62]. These results suggest that although the microbial diversity did not profoundly change during the experiment, the metabolic activity of the mat community may have been impacted in response to elevated pCO 2 .…”
Section: Changes In Ph During Environmental Manipulations and Impact mentioning
confidence: 75%
See 3 more Smart Citations
“…As outlined above, this pattern can easily be attributed to changes in fermentation patterns yielding different organic substrates (e.g., organic acids) available to the sulfate-reducing population. This change could have a major impact on the CaCO 3 precipitation by the microbial community [61,62]. These results suggest that although the microbial diversity did not profoundly change during the experiment, the metabolic activity of the mat community may have been impacted in response to elevated pCO 2 .…”
Section: Changes In Ph During Environmental Manipulations and Impact mentioning
confidence: 75%
“…A variety of different fermentation products have been found in cyanobacteria [63] and a shift in community metabolism, especially in fermentation pathways of the cyanobacteria, could have accounted for the drop in pH followed by an increase observed in the current study. Additionally, a shift of community metabolism to favor H 2 , formate, acetate and glycolate production could result in an increase in diversity and abundance of sulfate-reducing bacteria, accompanied by a slight increase in pH resulting from the metabolism of the anaerobic heterotrophs [62]. An argument based on modeling efforts was made that shifts in fermentation patterns would not affect the lithification potential [64,65] and further investigations are needed.…”
Section: Changes In Microbial Diversity In Response To Elevated Co 2 mentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfate-reducing bacteria, comprising a diverse assemblage representing many clades and various biochemical pathways, abet dolomitization under anoxic hypersaline conditions (Vasconcelos and McKenzie 1997). Depending on which organic substrate they use, sulfate-reducers may create alkaline conditions (high concentrations of dissolved inorganic carbon) favorable for the precipitation of calcium carbonate (Gallagher et al 2012) in a process analogous to diagenetic sulfate reduction in sediments where organic carbonates are precipitated (Schrag et al 2013;Canfield and Kump 2013). Although Meister (2013) has suggested that the (acidic) hydrogen ions released by sulfate reduction counteract the rise in alkalinity, thus potentially preventing precipitation of carbonate minerals, experiments on and models of microbial mineral formation indicate that sulfate-reducers, perhaps together with bacteria using other biochemical pathways, can precipitate carbonate minerals including calcium carbonate (Visscher et al 2000;Visscher and Stolz 2005;Bergmann et al 2013).…”
Section: Valve Thicknessmentioning
confidence: 99%